Correlation of Nutritional Status and Early Feeding with Post-Laparotomy Surgical Site Infection in Perforated Peptic Ulcer patients - Pradana, Ibrahim Risyad; Sulthana, Bambang Am'am Setya; Hapsari, Putie (Majalah Kedokteran Bandung, 2024)
A perforated peptic ulcer is an emergency requiring immediate treatment by laparotomy. Special attention needs to be established on systemic nutritional status. The postoperative early feeding is important to patients with preoperative non optimum nutritional status. This study aimed to examine the correlation between nutritional status, early feeding, and post-laparotomy surgical site infection in perforated peptic ulcer patients. This was a prospective observational study on 32 patients with perforated peptic ulcers underwent emergency laparotomy at Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from October 2021–2022. The nutritional status was assessed using Albumin, SGA. Eleven subjects had severe hypoalbuminemia and six subjects had severe malnutrition (SGA C). Early feeding was not performed on 7 subjects. The highest surgical wound infection rate was found on the 7th day with an incidence rate of 18.8%. Among patients experiencing infection, six (6) had SGA C  (p<0.001) and severe hypoalbuminemia (p=0.001) and 4 subjects were given early feeding (p=0.451). On the 14th day, Three SGA C and one SGA B experienced infection (p=0.01), while 3 subjects and 1 subjects who experienced infection had moderate hypoalbuminemia and severe hypoalbuminemia, respectively (p=0.16), Three subjects were not given early feeding p=0.01. On the 21st day to the 30th day, 1 subject with SGA C (p=0.10) and severe hypoalbuminemia (p=0.37), and early feeding was not performed (p>0.05). There is no association among albumin level, SGA, and early feeding in post-laparotomy wound infection in perforated peptic ulcer patients.